2010
DOI: 10.1111/j.1365-2427.2010.02537.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coupled natural and anthropogenic factors on the community structure of diadromous fish and shrimp species in tropical island streams

Abstract: 1. Overlapping river and road networks provide a framework for studying the complex interactions between natural and human systems, with river-road intersections as focal areas of study. Roads can alter the morphology of stream channels, pose barriers to freshwater fauna, provide easy access to streams for humans and non-native species and accelerate the expansion of urban development. 2. We determined what variables control the structure of diadromous fish and shrimp communities and assessed whether particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 59 publications
(117 reference statements)
1
36
0
6
Order By: Relevance
“…A major benefit for freshwater shrimps in the headwaters of streams on mountainous tropical islands is that there are few or no fish predators there (e.g., Covich et al, 2009;Blob et al, 2010;Hein et al, 2011). Covich et al (2009) (2007) suggested that an overall escape from predation by marine and estuarine fishes may have been an initial selective pressure favoring invasion of fresh water by groups that were capable of moving upstream.…”
Section: Evolutionary Origins Of Amphidromymentioning
confidence: 99%
“…A major benefit for freshwater shrimps in the headwaters of streams on mountainous tropical islands is that there are few or no fish predators there (e.g., Covich et al, 2009;Blob et al, 2010;Hein et al, 2011). Covich et al (2009) (2007) suggested that an overall escape from predation by marine and estuarine fishes may have been an initial selective pressure favoring invasion of fresh water by groups that were capable of moving upstream.…”
Section: Evolutionary Origins Of Amphidromymentioning
confidence: 99%
“…Decision and classification trees are a nonparametric approach to exploring complex systems (Davidson et al 2009, Hein et al 2011) and provide an alternative to generalized linear models (GLM) because of their ability to characterize hierarchical and nonlinear relationships and expose interactions among predictor variables (Michaelsen et al 1994). …”
Section: Decision Tree Analysis and Willingness To Sell Modelingmentioning
confidence: 99%
“…Por ejemplo, varias especies de camarones Macrobrachium spp. y Potimirin glabra, y peces (A. monticola, S. plumieri, A. tajasica) encontradas en quebradas y ríos costeros del Caribe centroamericano (Lorion, Kennedy & Braatne, 2011) y Las Antillas (Fievet, Doledec & Lim, 2001;Hein et al, 2011) han sido encontradas en muestreos en la ecorregión Darién (Álvarez-León, 1991; Agudelo-Zamora et al, 2010; C. Escobar-Sierra & J. F. Blanco, observ. pers.)…”
Section: Discussionunclassified
“…producción primaria) (Pringle, 1997;Ramírez & Hernández-Cruz, 2004;Hein et al, 2011). Debido a que la distribución de esta fauna diádroma es controlada principalmente por la presencia de cascadas y tramos de alta pendiente, la abundancia, biomasa y riqueza de insectos y camarones presentan discontinuidades aguas arriba y aguas debajo de estas geoformas (Pringle, 1997;Ramírez & Hernández-Cruz, 2004;Hein et al, 2011).…”
Section: Discussionunclassified